SEMANTOGRAFIK TARJIMA YOZUVINING LEKSIK, GRAMMATIK VA STILISTIK XUSUSIYATLARI («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
It is known that the interest in the issues of intercultural communication and the great attention to the work of consecutive translation require serious reforms in the field of translation. Based on this, it is necessary to reconsider the "art of translation" and the "process of teaching translation". These allow the self-learner to further develop their professional skills and develop translation skills that allow them to optimize translation problems.We know that a translator's ability to use language in the field of consecutive translation is one of the components of his competence that he has mastered this field. However, this qualification in him does not mean that he is a professional owner of the field, because today the demand for this field is changing day by day and is entering the stage of development. This article talks about new achievements in the field of translation studies, which is one of the important fields of applied linguistics, and more precisely, about the semantic recording of this activity, which is used in the process of consecutive translation. Semontography is a kind of translation writing, which serves the perspective of the science of translation studies. This individual translation record provides convenient options for the translator. Importantly, this type of translation record has its own capabilities and some features that distinguish it from other special types of record. So, the essence of the article is aimed at further development of consecutive translation activities in the field of translation studies, more precisely, at revealing the specific possibilities of the translation writing recommended for the representatives of this field, i.e. lexical, grammatical and stylistic features. In addition, in our article we intend to give some practical recommendations for learning a new script.Hence, a quick note in this translation activity is to record a speech of any length and have a special note that allows you to repeat it without losing the content.
Keywords: Semontography, semontagram, marking, IT, media, TJ, composition, affix, segment, index, coding, modeling, fixation, synchronization.